2009
DOI: 10.1158/1078-0432.ccr-09-0640
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Regulates Androgen Synthesis in Prostate Cancer Cells

Abstract: Purpose: The standard systemic treatment for prostate cancer patients is androgen deprivation therapy. Although serum testosterone concentrations were significantly reduced after androgen deprivation therapy, levels of intraprostatic androgens are reproducibly measured at concentrations sufficient to activate androgen receptor and stimulate tumor growth, suggesting that prostate cancer cells may survive androgen deprivation therapies by increasing intracrine androgen synthesis within the prostate. However, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 41 publications
2
79
0
Order By: Relevance
“…We focused on Th2 cytokines only because, previously, we observed that changes in Th2, and not Th1, cytokines better indicated effects on tumor burden/ response to therapy. A panel of Th2 cytokines, MCP-1, IL-4, IL-6, and IL-10 that are implicated in prostate cancer progression and pathology were selected (27)(28)(29)(30)(31)(32)(33)(34). Sera analyses showed a reduction in all mice given the combination regimen (Fig.…”
Section: Combination Therapy Results In Increased Apoptosis and Immunmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on Th2 cytokines only because, previously, we observed that changes in Th2, and not Th1, cytokines better indicated effects on tumor burden/ response to therapy. A panel of Th2 cytokines, MCP-1, IL-4, IL-6, and IL-10 that are implicated in prostate cancer progression and pathology were selected (27)(28)(29)(30)(31)(32)(33)(34). Sera analyses showed a reduction in all mice given the combination regimen (Fig.…”
Section: Combination Therapy Results In Increased Apoptosis and Immunmentioning
confidence: 99%
“…Although serum cytokines levels typically reflect the specific immune status of the host, a shift of the cytokine balance to Th2 has been shown to be associated with cancer progression (44,45). On this premise and to further test our previous finding that Th2 cytokines are a reliable predictor of tumor burden and treatment efficacy, we undertook an analysis of a panel of Th2 cytokines, MCP-1, IL-4, IL-10, and IL-6, that are implicated in prostate cancer progression, including development of androgen-refractory phenotype (27,(29)(30)(31)(46)(47)(48)(49)(50). In agreement with our previous findings (22), the reduced levels of serum Th2 cytokines, MCP-1, IL-4, and IL6 profiles ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical data support the biological role of the IL-6 pathway in prostate cancer, especially in an advanced castration-resistant prostate cancer patient where the significance of the IL-6 pathway is mediated by crosstalk between IL-6 and the AR pathway (9). Under androgen deprivation conditions, IL-6 is able to promote intracellular synthesis of androgens in the prostate (36), resulting in AR activation and upregulation of ARtargeted prostate specific antigen (PSA) expression, via STAT3 and MAPK signaling pathways (9), as well as an androgen enhancer region within the human PSA promoter (184).…”
Section: Interleukin-6mentioning
confidence: 98%
“…PSA values were also correlated with all hormone values at 6 months, but not at baseline (Takizawa et al 2010). IL-6, which is associated with advanced PCa, has also been linked with serum testosterone and DHEA among men treated with ADT (Chun et al 2009, Komatsu et al 2012. Steroidogenesis is higher in metastatic lesions, and this may also be stimulated by osteoclasts or extravesicle transport of CYP17 (Locke et al 2009, Jernberg et al 2013, Hagberg Thulin et al 2016.…”
Section: Biological Effects Of Sex Steroids Within the Prostate Cancementioning
confidence: 99%